MAQĀṢID-BASED SUSTAINABLE ISLAMIC EDUCATION IN MADRASAH: INTEGRATING LOCAL WISDOM, INCLUSIVITY, GLOBAL CITIZENSHIP, AND SOCIAL TRANSFORMATION - Sarifatul Jannah; Siti Aisah; Ahmad Halid; Yunita Wulandari (Academic Bright Collaboration, 2026)
This study analyzes how maqāṣid-based sustainable Islamic education can be developed in a madrasah by integrating local wisdom, inclusivity, global citizenship, and socio-religious transformation. It employed a qualitative descriptive case study supported by document analysis, observation guidelines, semi-structured interview protocols, student perception indicators, and thematic instrument mapping at MAS Darul Istiqomah Al Haya, Jember. The findings show that maqāṣid al-sharī‘ah functions as an ethical core for aligning religious formation, intellectual development, student safety, social responsibility, and resource stewardship. Local wisdom contextualizes Islamic values, inclusivity strengthens equitable learning, and global citizenship promotes tolerance, peace, environmental care, and social concern. The model offers practical guidance for madrasah leaders and teachers, but its empirical reach is limited to one institutional case and requires broader validation. The study contributes an interdisciplinary Islamic studies model that connects maqāṣid thought, Islamic education, local culture, inclusive pedagogy, and global social ethics. Article classification: empirical qualitative research.